RETRACTED: Assessment of threats to the economic security of the world’s leading countries within the framework of the global social and environmental agenda - Karanina E.V.; Lobanov V.I. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001